Ambient vibrational characterization of the Nossa Senhora das Dores Church. Issue 4 (2nd October 2017) - Mesquita, Esequiel; Brandão, Francisco; Diogenes, Aldecira; Antunes, Paulo; Varum, Humberto
Abstract: The present paper shows the vibrational characterization tests of a clay brick heritage construction from XIX century, the Nossa Senhora das Dores Church, placed in Sobral, Brazil. In this study the calibration of the 3D finite element numerical model of the church was performed through ambient vibrational testing using the first three natural frequencies identified. The obtained results, namely the natural frequencies identified, and the calibrated model intends to give a contribute for understanding of the structural behavior of the Brazilian heritage constructions, and introduces relevant information for be used for safety assessment of the church along the time.